Estimation of Silicon Nanocrystalline Sizes from Photoluminescence Measurements of RF Co-Sputtered Si/SiO2 Films - Ramírez Porras, Arturo (2003)
A stochastic distribution of nanocrystalline sizes model is applied to fit photoluminescence (PL) spectra of luminescent Si nanocrystals in a Si/SiO2 matrix synthesized by RF co-sputtering on the top of quartz substrates. With this method, the PL spectra from a diverse set of samples can be resolved mainly as the sum of two components: a contribution from a gaussian-like distribution of sizes of quantum dots (QD) and a similar component from a distribution of quantum wires (QW). These distributions of sizes and their associated PL energies agree well with the so-called Smart Quantum Confinement model (SQC).